Development of 2-Methoxyhuprine as Novel Lead for Alzheimer's Disease Therapy - Mezeiova, Eva; Korabecny, Jan; Sepsova, Vendula; Hrabinova, Martina; Jost, Petr; Muckova, Lubica; Kucera, Tomas; Dolezal, Rafael; Misik, Jan; Spilovska, Katarina; Pham, Ngoc Lam; Pokrievkova, Lucia; et al. (Molecules, 2017)
Tacrine (THA), the first clinically effective acetylcholinesterase (AChE) inhibitor and the first approved drug for the treatment of Alzheimer's disease (AD), was withdrawn from the market due to its side effects, particularly its hepatotoxicity. Nowadays, THA serves as a valuable scaffold for the design of novel agents potentially applicable for AD treatment. One such compound, namely 7-methoxytacrine (7-MEOTA), exhibits an intriguing profile, having suppressed hepatotoxicity and concomitantly retaining AChE inhibition properties. Another interesting class of AChE inhibitors represents Huprines, designed by merging two fragments of the known AChE inhibitors-THA and (-)-huperzine A. Several members of this compound family are more potent human AChE inhibitors than the parent compounds. The most promising are so-called huprines X and Y. Here, we report the design, synthesis, biological evaluation, and in silico studies of 2-methoxyhuprine that amalgamates structural features of 7-MEOTA and huprine Y in one molecule.
Keywords: Heterocyclic Compounds, 4 or More Rings; aktivace enzymů; Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; molekulární konformace; aminochinoliny; Aminoquinolines; Cell Line, Tumor; hydrolýza; Inhibitory Concentration 50; vazebná místa; Enzyme Activation; vazba proteinů; Molecular Structure; Structure-Activity Relationship; lidé; inhibiční koncentrace 50; Blood-Brain Barrier; Protein Binding; Molecular Conformation; hematoencefalická bariéra; Models, Molecular; molekulární struktura; takrin; Tacrine; molekulární modely; katalytická doména; acetylcholinesterasa; racionální návrh léčiv; Alzheimer Disease; Hydrolysis; Drug Discovery; permeabilita; Permeability; Drug Design; vztahy mezi strukturou a aktivitou; Alzheimerova nemoc; Cell Survival; viabilita buněk; cholinesterasové inhibitory; Cholinesterase Inhibitors; objevování léků; heterocyklické sloučeniny tetra- a více cyklické; Catalytic Domain; nádorové buněčné linie; Binding Sites; Humans